FREQUENCY OF PANTON VALENTINE LEUCOCIDIN GENE IN STAPHYLOCOCCUS AUREUS FROM SKIN AND SOFT TISSUE INFECTIONS - Akram, Asma; Izhar, Mateen; Lal, Chetan; Ghaffar, Hirra; Zafar, Saira; Saifullah, Asim; Yaseen, Adnan (Journal of Ayub Medical College Abbottabad, 2020)
Background: Staphylococcus aureus harbouring Panton Valentine Leucocidin gene are emerging and spreading worldwide. PVL gene was first identified by Noel Panton and Francis Valentine in 1932 who explained its ability to lyse leucocytes and its main relationship with skin and soft tissue infections. In Pakistan only limited data is available on the frequency and molecular analysis of PVL gene positive Staph aureus. Therefore, this study was conducted to understand the clinical epidemiology of PVL positive Staph aureus in our setup. Objectives of the study was aimed to determine the frequency of PVL gene in Staph aureus obtained from pus samples from skin and soft tissue infections from various departments; indoor and outdoor of a tertiary care hospital of Lahore. Methods: 384 Staph aureus isolates from skin and soft tissue infections were selected from both indoor and outdoor departments of hospital. After identification by phenotypic methods, they were processed by PCR using luk-F and luk-S primers for the detection of PVL gene. Results: 186 out of 384 Staph aureus isolates were positive for PVL gene. Overall frequency of PVL gene was 49%. Frequency of PVL gene in Staph aureus was 44.9% in males and 53.5% in females. The highest frequency of PVL gene was detected in paediatric age group. A large majority of positive isolates were from pus samples other than swabs and from the general surgery department. They mostly belong to indoor with indoor outdoor ratio of approximately 2:1. Frequencies of PVL gene in MRSA and MSSA were 51% and 44% respectively. Frequency of PVL gene was found to be high in Ciprofloxacin sensitive, Gentamicin sensitive, Erythromycin resistant and Fusidic acid resistant isolates. Conclusion: Almost half of Staph aureus isolates were found PVL positive. They were mostly multidrug resistant came from indoor setup. This situation is very alarming so, there is a need to adopt strict infection control policies in the hospitals to limit the widespread and injudicious use of antibiotics. There is also a need to apply PVL positive Staph aureus treatment to the effected individuals which involve not only antibiotics but also the decolonization of effected individuals and their close contacts. Keywords: Penton Valentine Leucocidin; Methicillin Resistant Staph aureus; Methicillin Sensitive Staph aureus; Multidrug Resistant; Polymerization Chain Reaction; Skin and Soft Tissue Infections